2014
DOI: 10.3855/jidc.3585
|View full text |Cite
|
Sign up to set email alerts
|

Ascaris lumbricoides infection and parasite load are associated with asthma in children

Abstract: Introduction: Association between Ascaris lumbricoides infection and asthma is a controversial subject that has been studied by several authors based on the hygiene theory. This work contributes to better understanding this issue. Methodology: This was a cross-sectional study involving 1,004 children from a neighborhood of low socioeconomic status in Campina Grande, Paraíba, northeastern Brazil. Asthma was diagnosed using the International Study of Asthma and Allergy in Childhood (ISAAC) questionnaire. Intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…It has been demonstrated that children from areas with high endemicity of infections with Ascaris lumbricoides , have low parasitic load of Ascaris lumbricoides , which becomes a protective factor against asthma manifestation and its symptoms. However, a high parasitic load is a risk factor, and contributes to high prevalence of severe asthma and its symptoms among these children [27]. Regarding the Th2 and Th17 triggered by the helminth infection, it is the same type of immune response found during the fibrogenesis process [28,29], but the role of both pulmonary fibrosis and ascariasis association remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that children from areas with high endemicity of infections with Ascaris lumbricoides , have low parasitic load of Ascaris lumbricoides , which becomes a protective factor against asthma manifestation and its symptoms. However, a high parasitic load is a risk factor, and contributes to high prevalence of severe asthma and its symptoms among these children [27]. Regarding the Th2 and Th17 triggered by the helminth infection, it is the same type of immune response found during the fibrogenesis process [28,29], but the role of both pulmonary fibrosis and ascariasis association remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to rural areas, it is common to find human ascariasis in both urban and rural environments because of the hardiness of Ascaris eggs ( 3 ). The major human morbidities from ascariasis include intestinal obstruction, malnutrition, growth stunting, and cognitive delays from the presence of adult worms in the gut, as well as asthma from Ascaris larval pulmonary migrations ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The human intestinal parasitic nematode causes the following problems to the human being Hookworm cause several abdominal pain, diarrhea, indigestion, loss of appetite nausea and vomiting, dysentery, constipation, and anemia while the chronic are abdominal pain kwashiorkor, and hypoproteinemia in addition to that, it is also leadng to the micronutrient deficiency 4 as well as even effectiong the eirly liner growm of children 5 , thus deworming is recommened to mainting the body nutrient contenst 6 . Ascaris lumbricoides the adult worm leading to blockage of intestinal lumen, absorption of the intestinal content, destruction of intestinal mucosa and peritonitis (rectal prolapsed), while larval migration breaks lungs capillaries causing hemorrhage, however, it can also act as protective factor to those suffering with asthma 7 . Trichuris trichiura Their heavy infection cause bloody diarrhea and rectal prolapsed is possible in severe cases.…”
Section: Introductionmentioning
confidence: 99%